BUSINESS STRATEGIES OF SMALL, AND MEDIUM ENTERPRISES (SMEs) TOWARDS POST-COVID-19 ADAPTATION: A CASE STUDY ON SMEs WEAVING CRAFTSMEN IN TANA TORAJA REGENCY - Kaleb Kurniawan Todingallo Payung; Saiful Mangngenre; Syarifuddin Mabe Parenreng (Journal of Industrial Engineering Management, 2022)
Adaptation of post-covid-19 pandemic changes is the government's plan in overcoming economic problems as a result of the Covid-19 pandemic. SMEs as one of the business sectors that most affected by the Covid-19 pandemic must have a business strategy so that they can revived by the adversity due to the pandemic and ready to face the post-covid-19 changes. This study using SWOT analysis to identify internal and external factors of SMEs Weaving in Tana Toraja Regency and formulate the right business strategy. TOPSIS method is used to rank alternative business strategies. Based on the SWOT analysis, there are four alternative business strategies formulated. The alternative business strategies are making woven product innovation, using digital marketing to sell the weaving products, using a business license to obtain capital for the development of a weaving business, creating a special tourist village for Toraja Weaving. Based on the output analysis of the scenario simulation results using the dynamic system method using Powersim 10 software, if the Weaving SMEs applies the four business strategies alternative, there will be an increase the profit value of weaving sales about 571% with a profit rate of Rp. 127,360,773.78 in a year.